Meningkatkan Kualitas Madrasah Melaui Pemberdayaan Peran Perpustakaan Belajar dari Cermin Sejarah - Ida Farida (Buletin Al-Turas, 2005)
As the heritage of Islam, Madrasahs contributed many aspects of life especially for Moslem intellectual development in thepast. Inevitable, the ability of madrasahs, such as Nizamiyah College, in contributing such Moslem intellectual developmentcould not be separated from the role of its libraries in supporting the learning process. Moslem at the time made libraries not merely storehouses of books but they performed an important role as centers of learning. Therefore, Moslem contemporary should learn the spirit and factual experience of Moslem in the past in the promotion of literacy and libraries in developing human intelligence to create a center of excellence for Islamic education